Desain Video Pembelajaran Matematika dalam Menghadapi Pandemi - Lisa Ririn Handayani; Anggun Badu Kusuma (Universitas Veteran Bangun Nusantara, 2022)
During a pandemic like now, learning is done online. One of the media that is often used in online learning is learning videos. The purpose of writing this article is to examine the design of mathematics learning videos with Problem-solving, Problem Based Learning, and Brain-Based Learning models to deal with the pandemic. This article is the result of a literature review with the source of the study in the form of a journal article that discusses the design of mathematics learning videos. The results of this study include (1) problem-solving-based learning videos developed and designed to suit the characteristics of students to make it easier for students to understand the material presented in the video; (2) Problem Based Learning-based learning videos in their presentation using moving images and choosing the right colors can increase students' enthusiasm for learning; (3) Brain-Based Learning-based learning videos are designed by providing related facts/daily events related to learning materials.